2005
DOI: 10.1002/jmv.20486
|View full text |Cite
|
Sign up to set email alerts
|

Changes in risk behavior and dynamics of hepatitis C virus infections among young drug users in Amsterdam, the Netherlands

Abstract: To elucidate the character and magnitude of the hepatitis C virus (HCV) epidemic among drug users in Amsterdam, 197 young drug users from the period 2000 to 2004 were compared with 215 counterparts from 1985 to 1989. Although injection risk behavior and HCV seroprevalence decreased sharply over time, HCV seroprevalence remains high (44%) among young drug users who have ever injected. Phylogenetic analysis shows that current HCV infections originate from diversification of strains already circulating in the pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
62
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 41 publications
1
62
0
Order By: Relevance
“…It reflects the cumulative exposure to infected needles and injection paraphernalia. On the other hand, sharing syringes was not identified as a risk factor; a similar result to that observed in Van de Laar et al [19].…”
Section: Discussionsupporting
confidence: 87%
“…It reflects the cumulative exposure to infected needles and injection paraphernalia. On the other hand, sharing syringes was not identified as a risk factor; a similar result to that observed in Van de Laar et al [19].…”
Section: Discussionsupporting
confidence: 87%
“…All AHS participants were part of surveys performed to monitor the general population or specific risk groups for the presence of sexually transmitted and blood-borne infections. AHS establishes the HCV genotype using an in-house PCR targeting the HCV core region (33). AMC uses a commercial 5Ј untranslated region-based HCV genotyping assay (Trugene 5ЈNC; Genelibrarian module 3.1.2; Bayer Healthcare, Berkeley, CA).…”
Section: Methodsmentioning
confidence: 99%
“…NS5B PCR 2. NS5B fragment 2 (436 bp, nucleotides 8206 to 8642) was amplified by a nested PCR assay, as described by van de Laar et al (33). The composition of the reaction mixture and the cycling conditions were identical to those described above, except some modifications were made so that 3 l cDNA instead of 3 l RNA could be used as the input for the first-round PCR.…”
Section: Methodsmentioning
confidence: 99%
“…These lineages fall within the greater African diversity, but the extent of their divergence suggests dissemination from Africa before the rise of global travel and modern medicine (20). During the 20th century, transmission via contaminated blood, blood products, invasive procedures, and IDU eventually resulted in the global dispersal of HCV-2, particularly subtypes 2a and 2b, which cause the vast majority of HCV-2 infections in developed countries (9,11,44). Interestingly, two recent studies from France revealed a wide variety of HCV-2 subtypes, including among the native French population (5,40).…”
mentioning
confidence: 99%